Ribavirin and its analogs: Сan you teach an old dog new tricks? - M. V. Chudinov (Тонкие химические технологии, 2019)
The review article focuses on the current state of synthetic and biological studies of ribavirin analogs. Ribavirin is a broad-spectrum nucleoside antiviral drug with a 50-year long history of research and application, but its mechanism of action still remains unclear. This article examines contemporary views on the antiviral and antitumor effects of ribavirin and its analogs and describes the contradictions and gaps that exist in our knowledge. In recent years, new nucleoside analogs of ribavirin have been synthesized. These ribavirin derivatives modified at the heterocyclic base, have the potential to become the antiviral and antitumor agents of the new generation. Thus, this paper presents a systematic review of antiviral activities, antitumor activities and structure–activity relationship (SAR) correlations of 39 ribavirin analogs created in the past 15 years. Biological targets and possible mechanisms of action of these new compounds are also discussed, as well as the prospects and possible directions for further research.